2014
DOI: 10.1111/aogs.12379
|View full text |Cite
|
Sign up to set email alerts
|

Women with greater pelvic floor muscle strength have better sexual function

Abstract: Our findings suggest that women with stronger pelvic floor muscles have better sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 22 publications
6
56
1
11
Order By: Relevance
“…Although the results of non-randomised studies suggest that improvement in PFMS would improve SF [46,47], this has not been clearly demonstrated in this review. Most RCTs did not analyse this association, and conflicting results were found between one study that did not establish this association [11] and one study that found a medium and small correlation between changes in SF and PFMS, respectively [14].…”
Section: Discussionmentioning
confidence: 62%
“…Although the results of non-randomised studies suggest that improvement in PFMS would improve SF [46,47], this has not been clearly demonstrated in this review. Most RCTs did not analyse this association, and conflicting results were found between one study that did not establish this association [11] and one study that found a medium and small correlation between changes in SF and PFMS, respectively [14].…”
Section: Discussionmentioning
confidence: 62%
“…Some studies show a positive association between strength of pelvic floor muscle (PFM) and sexual function (12,13). It is believed that the pelvic floor muscles have an important role in creating involuntary contractions in women during intercourse by strengthening vaginal lining, increasing blood flow to the genitalia, as well as being responsible for the sensitivity felt by couples during sexual activity (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Mais da metade (56,2%) autodeclarou-se parda e a maioria referiu ensino médio completo (78,9%), trabalho remunerado (73,5%) e coabitação com o parceiro (86,7%), sendo esta há mais de um ano em 83,8 % dos casos (Tabela 1). Embora alguns estudos sugiram que a idade materna não está relacionada à FMAP (Costa, 2008;Caroci, 2014;Martinez et al, 2014) Vale comentar que, embora neste estudo não tenha sido encontrada diferença estatisticamente significante na FMAP entre os grupos que realizaram ou não os exercícios perineais durante a gestação e após o parto, estudos vêm apontando os benefícios dos exercícios perineais para os músculos do AP (Mørkved et al, 2003;Dinc;Beji;Yalcin, 2009). …”
Section: Caracterização Das Participantesunclassified